Produção científica em bioética no campo da enfermagem: revisão integrativa da literatura - Nogueira, Matheus Figueiredo (2009)
Considering the importance of socializing the knowledge produced by researchers of nursing in the field of bioethics, this study has as objectives to synthesizes scientific productions of nursing in the field of the bioethics in the period from 2000 to 2008, identify the thematic approached in the studies selected for the investigation proposed, investigate the contributions of the scientific productions of the nursing in the field of bioethics to endorse the professional practice, and check the academic formation, title and the performance area of the researchers of the publications of nursing in the field of the bioethics. It is an integrative review of the literature, investigation modality, which allows to build up a large analysis of the literature where conclusions of studies previously conducted are summarized aiming inferences be formulated about an specific topic. To identify the studies published in the area of Nursing and Bioethics an online search was done and the sample was composed of 46 studies. The results point out that the base SciELO provided 43.4% of the publications, the Magazine World Health stood out with 21.7% of the publications included in this review, researchers are represented mostly by doctors nurses, representing 32.6% of the total; on the field of professional performance, the one which most highlighted was the nurses who are teaching in the levels of undergraduate and postgraduate degrees, with 42.0% of the total of professionals. About the issue approached in the studies, it was possible to determine similarities and differences between the discussions proposed by the studies, which prompted the construction of eight thematic approaches (TA) as prerequisite for integrative review, they are: TA 1 - Bioethics, Nursing and scientific technologic development, TA 2 Bioethics Reflections and Ethical Conflicts in Health Care, TA 3 - Bioethics and Research Involving Human beings, TA 4 - Bioethics and End of life of Life; TA 5 - Bioethics and Teaching in the Field of Nursing, TA 6 Bioethics and Rights of Users of Health Services, TA 7 - Bioethics as Reflection Instrument in the Field of Health, and TA 8 Bioethics as guideline for the Practice of Nursing. Identified, therefore, that the studies published by researchers of nursing allow a solid understanding of bioethics is anchored to the various situations of professional practice. The analysis of the research provided to highlight countless contributions to nursing practice, which, briefly, indicate that the nursing professional acknowledges bioethics as a field of reflection to their practice, guiding their actions from the principles of autonomy, justice, beneficence and no harm, since the professional ethical action involves more than the performance of procedures and techniques. Therefore, it is essential to ensure that the practices, interpersonal relationships and the decisions taken, bioethical reflection serves as a liaison to ensure respect for the rights and the preservation of human dignity. Thus, it is necessary to encourage researchers to develop new nursing studies that address bioethical approaches to provide subsidies for the qualification, integrity and civility in the actions of nursing.